Effects of Health Qigong on cervical spondylosis: a systematic review - Liu, Cong; Soh, Kim Geok; Loh, Su Peng; Sun, He; Soh, Kim Lam; Ma, Yujin; Ma, Hucheng (Churchill Livingstone, 2025)
Aim: Exercise therapy is a widely utilized intervention for the prevention and rehabilitation of cervical spondylosis. As a distinctive form of traditional exercise therapy in China, Health Qigong has been empirically validated to exert beneficial effects across 17 physiological systems, with particularly pronounced efficacy in addressing musculoskeletal disorders. This systematic review aims to critically evaluate the impact of Health Qigong on cervical spondylosis. Methods: According to the literature search principles, works published from the publication date to November 2024 were searched. The databases used were the China National Knowledge Infrastructure, Scopus, PubMed, Web of Science, and EBSCOhost (SPORTDiscus). The study quality was evaluated using the Physiotherapy Evidence Database (PEDro) scale. The search process was documented using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA)2020. Results: A total of 10 studies were selected from an initial pool of 702 studies, comprising 656 participants. The PEDro scores of the 10 studies ranged from seven to eight. The findings indicate that Health Qigong exerts its therapeutic effects on cervical spondylosis primarily in four key areas: alleviating neck pain, improving cervical dysfunction, restoring cervical curvature, and enhancing cervical mobility. Specifically, for pain relief, the Visual Analog Scale(VAS) scores showed a mean reduction of 2.8–4.15 points, while the Neck Disability Index (NDI) scores significantly decreased from 6.10 to 1.4. And after intervention, the prevalence of abnormal cervical curvature decreased by 10.97 %, cervical range of motion (CROM) improved by 19.78° to 67.4° on average. Furthermore, according to the Traditional Chinese Medicine (TCM) Diagnostic and Treatment Criteria, five studies reported an overall effectiveness rate exceeding 90 %, with a maximum of 97.14 %. Short-term intervention outcomes indicated that Ba Duan Jin showed a recurrence rate of 0 %, whereas interventions using Yi Jin Jing and Wu Qin Xi exhibited recurrence rates ranging from 11.2 % to 13.33 %. Conclusion: As an exercise-based intervention, Health Qigong not only helps alleviate cervical spondylosis-related pain and improve cervical dysfunction but also promotes the restoration of cervical curvature and enhances cervical mobility, thereby addressing limitations in neck function. However, current research exhibits certain limitations and research gaps in areas such as populations, cervical spondylosis classification, intervention design, and outcome assessment criteria.Therefore, there is an urgent need to develop more targeted intervention strategies, establish standardized outcome evaluation systems, and conduct in-depth mechanistic studies to further validate the clinical efficacy and practical application of Health Qigong in the management of cervical spondylosis.